Cortical Bcl-2 protein expression and apoptotic regulation in schizophrenia - Jarskog, L.Fredrik; Gilmore, John H; Selinger, Elzbieta S; Lieberman, Jeffrey A (Biological psychiatry (1969), 2000)
Background: The etiology of schizophrenia remains unknown; however, a role for apoptosis has been hypothesized. Bcl-2 is a potent inhibitor of apoptosis and also exerts neurotrophic activity in the central nervous system (CNS). Bcl-2 expression is increased in the CNS of several neurodegenerative disorders. Given that schizophrenia has certain features of a limited neurodegenerative disorder, it was hypothesized that cortical Bcl-2 expression is increased in schizophrenia. Methods: Postmortem temporal cortex was obtained from the Stanley Foundation Neuropathology Consortium with matched control, schizophrenic, bipolar, and depressed subjects. Bcl-2 protein was measured by enzyme-linked immunoassay (ELISA) and Western blot. Primary analysis was limited to schizophrenia versus control subjects. Results: The ELISA demonstrated 25% less Bcl-2 protein in schizophrenia ( p = .046), supported by Western blot results. A secondary analysis of schizophrenic and bipolar subjects revealed twofold higher mean Bcl-2 in antipsychotic-treated versus neuroleptic-naive subjects. Conclusions: Contrary to our hypothesis, cortical Bcl-2 was reduced in schizophrenia. This supports the notion that schizophrenia is not a classic neurodegenerative disorder; however, less Bcl-2 protein may signal neuronal vulnerability to proapoptotic stimuli and to neuronal atrophy. Also, the association between neuroleptic exposure and higher Bcl-2 levels could underlie the favorable long-term outcomes of patients who receive maintenance antipsychotic treatment.